Kidney and gallbladder stones and the risk of prostate cancer: Results from the EPICAP study - Melissa Sawaya; Emilie Cordina-Duverger; Pierre-Jean Lamy; Brigitte Trétarre; Florence Menegaux (PLoS ONE, 2025)
Background Prostate cancer remains the most frequent cancer among men, representing a significant health burden. Despite its high morbidity and mortality rates, the etiology of prostate cancer remains relatively unknown, with only non-modifiable established risk factors. Chronic inflammation has emerged as a potential factor in prostate carcinogenesis. We investigated the role of kidney and gallbladder stones and the risk of prostate cancer. Methods We used data from EPICAP, a population-based case-control study. A total of 819 diagnosed prostate cancer cases and 879 controls were face-to-face interviewed using a standardized questionnaire that collected information on personal medical history, including history of kidney and gallbladder stones. Odds Ratios (OR) and their 95% confidence interval (CI) were estimated using multivariate unconditional logistic regression. Results Our study revealed intriguing patterns regarding kidney and gallbladder stones in relation to prostate cancer risk. The analysis indicated significant potential associations between kidney stones and the risk of prostate cancer (OR: 1.46 95% CI: 1.13–1.90), particularly in men with a history of kidney infection. Additionally, our data suggested a possible relationship between gallbladder stones and prostate cancer when considering triglyceride (OR: 2.27, 95% CI: 0.99–5.28), although further research is needed for a conclusive understanding. Conclusions Our results suggest an association between calculi and the risk of prostate cancer. Findings from this study underscore the need for a more comprehensive investigation to understand the role of chronic inflammation or metabolism and delineate the mechanisms underlying these potential associations in order to guide the development of targeted preventive strategies for aggressive prostate cancer.